In vitro Chicken Bone Marrow-Derived Dendritic Cells Comprise Subsets at Different States of Maturation - van den Biggelaar, Robin H. G. A.; Arkesteijn, Ger J. A.; Rutten, Victor P. M. G.; van Eden, Willem; Jansen, Christine A. (Frontiers in Immunology, 2020)
Research in chickens has been fundamental for the discovery of basic aspects of the immune system and has led to an interest in the in-depth characterization of avian immune cell types including dendritic cells (DCs). The in vitro generation and expansion of chicken bone marrow-derived dendritic cells (chBMDCs) in the presence of GM-CSF has provided a way to study chicken DCs, which are only present at limited cell numbers in vivo. This method has been employed to study the interactions between chicken DCs and pathogens or vaccines. However, a detailed characterization of the chBMDC culture was still lacking. In the present study, we performed an elaborate phenotypical and functional analysis of the chBMDC culture and addressed its heterogeneity. After 8 days of culture, chBMDCs comprised MHC-IIlow and MHC-IIhigh subsets with different morphologies. Compared to MHC-IIlow chBMDCs, the MHC-IIhigh subset showed a more mature phenotype, with higher expression of CD1.1, CD40, CD80, CCR7, and CD83, and a relatively low opsonophagocytic capacity. Nevertheless, MHC-IIhigh chBMDCs did not show an increased capacity to induce T cell proliferation. Therefore, MHC-IIhigh chBMDCs were found to be semi-mature. Interestingly, the presence of the semi-mature MHC-IIhigh chBMDCs subset reduced when cells were cultured in the presence of IL-4. Finally, prolonged cell culture after FACS-sorting converted the semi-mature MHC-IIhigh subset back into the immature phenotype of the MHC-IIlow subset, demonstrating plasticity of their maturation state. This detailed characterization explained the heterogeneity of the chBMDC culture by the simultaneous presence of immature and semi-mature chBMDC subsets, in addition to cells without features of antigen-presenting cells. Our findings are instrumental for the interpretation of experiments using the chBMDC culture in past and future research by providing insights into its phenotypically and functionally distinct cell types.